Aktivitas Penghambat Reseptor-β Adrenergik Ekstrak Air Kulit Batang Taya (Nauclea subdita (Korth) Steud) Pada Tikus Wistar Jantan - Erfan Tri Prasongko; Finna Setiawan; Christina Avanti (Fakultas Farmasi Universitas Pancasila, 2020)
Beta-adrenergic receptor blockers (β-blockers) are an appropriate treatment for patients with hypertension who have concomitant ischemic hearat disease, heart failure, obstructive cardiomyopathy, aortic dissection or certain cardiac arrhythmias. Taya (Nauclea subdita (Korth) Steud) is a local natural potential of Kalimantan that is empirically believed to have antihypertensive activities. This study aims to determine the activity of β-adrenergic receptor inhibitors of stem bark water extract in male wistar rats. Tests were carried out on male Wistar rats by the Non Invasive Blood Pressure method using the CODA® tool. Test animals were divided into 5 groups: normal group, induction group (Epinephrine 1.2 µg/kgBW), 100 mg/kgBW extract group, 200 mg/kgBW extract group, and 4,5 mg/kgBW atenolol group. The induction group showed an increase in systolic blood pressure, diastolic blood pressure, and heart rate that were significantly different from the normal group, the 100 mg/kgBW extract group, the 200 mg/kgBW extract extract group, and the 4.5 mg/kgBW atenolol group (p<0,05). The 100 mg/kgBW extract group was not significantly different from systolic blood pressure, diastolic blood pressure, and heart rate with the normal group, the 200 mg/kgBW extract group, and the 4.5 mg/kgBW atenolol group (p> 0.05). The results of this study showed that taya bark water extracts 100 mg/kgbw had inhibitory activity of β-adrenergic receptors in male wistar rats.